2010
DOI: 10.1590/s1516-44462010000600007
|View full text |Cite
|
Sign up to set email alerts
|

Manejo do paciente com transtornos relacionados ao uso de substância psicoativa na emergência psiquiátrica

Abstract: OBJETIVO: Transtornos por uso de substâncias são prevalentes em setores de emergência gerais e psiquiátricos, atingindo taxas de 28% das ocorrências em prontos-socorros gerais. Todavia, profissionais dos setores de emergência identificam menos que 50% dos casos de problemas relacionados ao álcool. Este artigo visa fornecer base fundamentada em evidências para o tratamento específico a pacientes que preencham os critérios diagnósticos de transtornos por uso de substâncias e que se apresentam ao pronto-socorro e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
12

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 33 publications
0
10
0
12
Order By: Relevance
“…and the necessary stabilization of the patient (Del-Ben, Rufino, Azevedo-Marques, & Menezes, 2010), assisting in the reduction of risks to themselves or others, adjusting their pharmacological treatment (Amaral, Malbergier, & Andrade, 2010) and providing tests and additional examinations, sometimes required by the construction of differential diagnosis or clarification of clinical questions (Cardoso & Galera, 2011).…”
mentioning
confidence: 99%
“…and the necessary stabilization of the patient (Del-Ben, Rufino, Azevedo-Marques, & Menezes, 2010), assisting in the reduction of risks to themselves or others, adjusting their pharmacological treatment (Amaral, Malbergier, & Andrade, 2010) and providing tests and additional examinations, sometimes required by the construction of differential diagnosis or clarification of clinical questions (Cardoso & Galera, 2011).…”
mentioning
confidence: 99%
“…Amaral et al found that 28% of all patients in medical emergency units had substance use disorders, but less than half of the patients with alcohol-related problems were identified [12]. …”
Section: Discussionmentioning
confidence: 99%
“…Bulgular uyuşukluk, koordinasyon güçlüğü, düşünmede zorlanma, hafıza zayıflığı, konuşmada ve anlamada güçlük, yanlış algılama, seksüel ve agresif dürtülerin disinbisyonu, emosyonel labilitedir. Uyuşukluk birkaç saatte geçse de motor becerilerdeki, yargılamadaki ve duygudurumdaki bozulma 12 ila 24 saat devam edebilir (29).…”
Section: Benzodiazepinler Entoksikasyonunclassified
“…Barbutiratlar güvenlik indeksi düşük ilaçlar olduklarından son yıllarda daha az tercih edilmektedirler. Bunun yerine ya hastayı kullandığı benzodiazepini günlük dozundan %10 azaltarak kesmek ya da eğer hasta kısa etkili benzodiazepin kullanıyorsa bunun yerine uzun etkili benzodiazepine geçmek ve daha sonra bu yeni ilacın dozunu azaltarak sonlandırmak önerilebilir (29).…”
Section: Yoksunlukunclassified